ANALISIS PERBANDINGAN KINERJA KEUANGAN PT. BANK BRI SYARIAH DAN PT. BANK BNI SYARIAH PERIODE 2015-2019 - Oktaviani, Amelia; Trihantana, Rully; Kusumaningrum, Ria (Jurnal Penelitian Perbankan Syariah: Program Studi Perbankan Syariah., 2023)
In carrying out economic activities, people prefer to do it in healthy financial institutions (banks), so that a bank will better guarantee various forms of transactions or economic activities in the people who are its customers. Bank health assessment aims to determine whether a bank is in a healthy or unhealthy condition. To determine whether a bank is in a healthy or unhealthy condition, an assessment can be carried out through the Bank Health Level Assessment System. The health of banking financial institutions is in the interests of all parties involved, including bank owners and managers as well as service users or customers. Fluctuating profits from year to year at PT. BRI Syariah Bank and PT. BNI Syariah Bank has an impact on the good and bad of a bank's health and will also influence customers to use the bank's services, as well as investors who will invest their capital. Therefore, this research was created to determine the level of bank health using the CAMEL (Capital, Asset Quality, Management, Earning, and Liquidity) method and to determine the comparison of financial performance between BRI Syariah and BNI Syariah. The data analysis tool in this research uses quantitative descriptive analysis which takes data from the Annual Report of BRI Syariah and BNI Syariah from 2015 to 2019. Data processing uses analysis prerequisite tests (data normality test, multicollinearity test, autocorrelation test, heteroscedasticity test) and Hypothesis testing (independent sample t-test, partial test, simultaneous test, multiple linear regression test) with the help of the SPSS application program. The conclusion of this research is that there are several differences in the magnitude of the ratios between BRI Syariah and BNI Syariah seen from the results of the independent sample t-test, namely the average value of BRI Syariah CAR 21,968, KAP 1,038, NPM 4,700, ROA 5,574, FDR 78,612 and the average value -average BNI Syariah CAR 21,922, KAP 1,052, NPM 5,580, ROA 13,540, FDR 82,130. Thus, looking at the overall ratio value of the two banks, it can be concluded that BNI Syariah performed better than BRI Syariah from 2015 to 2019.